2016
DOI: 10.1155/2016/3125283
|View full text |Cite
|
Sign up to set email alerts
|

Psychomotor Development in Cri du Chat Syndrome: Comparison in Two Italian Cohorts with Different Rehabilitation Methods

Abstract: The Cri du Chat syndrome (CdC) is a rare genetic disorder caused by variable size deletions of the short arm of chromosome 5 (5p−). It is well known that home-reared patients show better performances as compared to institutionalised cases, and it was reported that continuous educational intervention can ameliorate their performances. To assess the efficacy of educational intervention and to develop new CdC oriented programs of rehabilitation, we compare the results obtained for many developmental skills in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Furthermore, 81.9% of the patients were diagnosed in the first year of life, and it was reported that 71.6% of the patients started physiotherapy before one year-old in the same study. 9 Although patients who started physiotherapy before one year-old are indicated to have better results in the achievement of developmental skills, there was no statistical 9 Guala et al 26 who carried out another study, investigated the effect of two rehabilitation programs on the development and reported that no significant difference was found. There are several findings concerning physiotherapy, 9,26 but some information in these studies is unclear, such as specific and detailed information about the physiotherapy, the child's initial functional levels, and age of onset of physiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 81.9% of the patients were diagnosed in the first year of life, and it was reported that 71.6% of the patients started physiotherapy before one year-old in the same study. 9 Although patients who started physiotherapy before one year-old are indicated to have better results in the achievement of developmental skills, there was no statistical 9 Guala et al 26 who carried out another study, investigated the effect of two rehabilitation programs on the development and reported that no significant difference was found. There are several findings concerning physiotherapy, 9,26 but some information in these studies is unclear, such as specific and detailed information about the physiotherapy, the child's initial functional levels, and age of onset of physiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac and renal malformations may be also found [ 4 ]. There is no specific treatment for CdC nevertheless, patients benefit from rehabilitative programs, which should be started as soon as possible and involve close collaboration with families, who must be supported psychologically [ 5 ]. Moreover, it is required that clinical evaluations take place regularly over the course of a person’s life, more specifically from the neonatal to adulthood period [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cr i du chat syndrome (CDCS) is a rare genetic disease with an incidence ranging from 1 in 15,000 to 1 in 50,000 live births, caused by either a partial or a complete deletion of chromosome 5p (1). The clinical phenotype depends on the location and extent of the genomic region involved in the 5p deletion, with the breakpoint location varying from p13 (D5S763) to p15.2 (D5S18) (2)(3)(4)(5). The various phenotypes are characterized by different degrees of severity in the developmental and behavioral problems associated with the disease.…”
mentioning
confidence: 99%
“…The various phenotypes are characterized by different degrees of severity in the developmental and behavioral problems associated with the disease. Physical and behavioral characteristics include a high-pitched cry, microcephaly, a broad nasal bridge, epicanthal folds, micrognathia, and severe psychomotor retardation (2). Diagnosis is based on clinical manifestations and requires karyotyping, array comparative genomic hybridization, and, eventually, fluorescence in situ hybridization for doubtful cases (1,2).…”
mentioning
confidence: 99%
See 1 more Smart Citation